2017
DOI: 10.18203/issn.2455-4529.intjresdermatol20172210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prescribing pattern and quality of life of dermatology patients by using dermatology quality life index

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">The goal of the study was to assess the prescribing pattern, pattern of skin diseases among the patients and to assess the impact of quality of life in various Skin diseases of dermatological patients by using dermatological quality life index (DLQI). The present study aims at improving the patient’s knowledge towards their disease and medication and also to measure the improvement of Quality of life of patients.</sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…QoL. This finding is similar to that obtained in another study carried out by Sangeetha T et al9 in India, as well as in other countries by Al-Hoqail IA et al10 , and Tejada CD et al11 with scores ranging from 6.73 to 8.32.This study found higher mean DLQI scores for patients who were younger in age, probably because, younger individuals were more frequently affected by physical symptoms like itching and pain along with embarrassment caused by skin lesions at their school and work. This finding was consistent with Mean scores in different Domains of DLQI questionnaire…”
supporting
confidence: 92%
“…QoL. This finding is similar to that obtained in another study carried out by Sangeetha T et al9 in India, as well as in other countries by Al-Hoqail IA et al10 , and Tejada CD et al11 with scores ranging from 6.73 to 8.32.This study found higher mean DLQI scores for patients who were younger in age, probably because, younger individuals were more frequently affected by physical symptoms like itching and pain along with embarrassment caused by skin lesions at their school and work. This finding was consistent with Mean scores in different Domains of DLQI questionnaire…”
supporting
confidence: 92%
“…Irrational drug combinations, over use of multivitamins, emollients, unnecessary use of antibacterial in fungal infections and prescribing drug from same class led to the unnecessary skin diseases. 7…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, green addition agents are popularly used as additional agents in the electrodeposition process. Felicita et al [7][8][9][10][11][12][13][14] used several novel green extracts normally containing carbonyl compounds as major component as additives. The present work aims to study the effect of Ananas comosus juice on nickel electrodeposition.…”
Section: Introductionmentioning
confidence: 99%